Booster vaccination against tetanus and diphtheria: insufficient protection against diphtheria in young and elderly adults. Issue 1 (December 2016) - Grasse, Marco; Meryk, Andreas; Schirmer, Michael; Grubeck-Loebenstein, Beatrix; Weinberger, Birgit
Abstract We have recently demonstrated that single shot vaccinations against tetanus and diphtheria do not lead to long-lasting immunity against diphtheria in elderly persons despite administration at 5 year intervals. In the present study we have immunized a group of young adults against tetanus and diphtheria to compare the pre- and 28 days post-vaccination immune responses in the young group with results of the same vaccination performed in an elderly group of a previous study. We also studied protection in both groups 5 years after vaccination. We compared antibody titers at all three time points and also analyzed the T cell responses in both age groups 5 years after vaccination. Before vaccination 9 % of the elderly persons were not protected against tetanus, and 48 % did not have protection against diphtheria. In the young group all participants were protected against tetanus, but 52 % were also unprotected against diphtheria before vaccination. 28 days after vaccination 100 % of all participants had protective antibody concentrations against tetanus and only a small percentage in each age group (<10 %) was unprotected against diphtheria. 5 years later, 100 % of both cohorts were still protected against tetanus, but 24 % of the young and 54 % of the elderly group were unprotected against diphtheria. Antibody concentrations against diphtheria measured by ELISA correlated well with their neutralizing capacity. T cell responses to tetanus and diphtheria did not differ between young and old persons. We conclude that booster vaccinations against tetanus and diphtheria according to present recommendations provide long-lasting protection only against tetanus, but not against diphtheria, independently of age. In elderly persons, the level of protection is even lower, probably due to intrinsic age-related changes within the immune system and/or insufficient vaccination earlier in life.